Tumor characteristics associated with engraftment of patient‐derived non–small cell lung cancer xenografts in immunocompromised mice. Issue 21 (9th July 2019) - Chen, Yungchang; Zhang, Ran; Wang, Li; Correa, Arlene M.; Pataer, Apar; Xu, Yi; Zhang, Xiaoshan; Ren, Chenghui; Wu, Shuhong; Meng, Qing H.; Fujimoto, Junya; Jensen, Vanessa B.; et al.
Abstract : Background: Patient‐derived xenograft (PDX) models increasingly are used in translational research. However, the engraftment rates of patient tumor samples in immunodeficient mice to PDX models vary greatly. Methods: Tumor tissue samples from 308 patients with non–small cell lung cancer were implanted in immunodeficient mice. The patients were followed for 1.5 to approximately 6 years. The authors performed histological analysis of PDXs and some residual tumor tissues in mice with failed PDX growth at 1 year after implantation. Quantitative polymerase chain reaction and enzyme‐linked immunoadsorbent assay were performed to measure the levels of Epstein‐Barr virus genes and human immunoglobulin G in PDX samples. Patient characteristics were compared for PDX growth and overall survival as outcomes using Cox regression analyses. Disease staging was based on the 7th TNM staging system. Results: The overall engraftment rate for PDXs from patients with non–small cell lung cancer was 34%. Squamous cell carcinomas had a higher engraftment rate (53%) compared with adenocarcinomas. Tumor samples from patients with stage II and stage III disease and from larger tumors were found to have relatively high engraftment rates. Patients whose tumors successfully engrafted had worse overall survival, particularly those individuals with adenocarcinoma, stage III or stage IV disease, and moderately differentiated tumors. Lymphoma formation was one of the factors associated with engraftment failure. Human CD8‐positive and CD20‐positive cells were detected in residual samples of tumor tissue that failed to generate a PDX at 1 year after implantation. Human immunoglobulin G was detected in the plasma of mice that did not have PDX growth at 14 months after implantation. Conclusions: The results of the current study indicate that the characteristics of cancer cells and the tumor immune microenvironment in primary tumors both can affect engraftment of a primary tumor sample. Abstract : The results of the current study demonstrate that clinical tumor characteristics, biological features of cancer cells, and the tumor immune microenvironment are associated with successful engraftment of tumor samples. Patients' immune cells can be present for a long time in residual tissue from failed patient‐derived xenografts (PDXs), which indicates that these immune cells may play a role in inhibiting PDX engraftment.